2005
DOI: 10.1074/jbc.m504710200
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Locked Synthetic Bilin Derivatives and Phytochrome Agp1 from Agrobacterium tumefaciens Form Photoinsensitive Pr- and Pfr-like Adducts

Abstract: Phytochrome photoreceptors undergo reversible photoconversion between the red-absorbing form, Pr, and the far-red-absorbing form, Pfr. The first step in the conversion from Pr to Pfr is a Z to E isomerization around the C15‫؍‬C16 double bond of the bilin chromophore. We prepared four synthetic biliverdin (BV) derivatives in which rings C and D are sterically locked by cyclizing with an additional carbon chain. In these chromophores, which are termed 15Za, 15Zs, 15Ea, and 15Es, the C15‫؍‬C16 double bond is in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
106
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 39 publications
15
106
3
Order By: Relevance
“…The wild-type BV adduct is shown in the Pr state (solid) and as a calculated pure Pfr spectrum (dashed line). Figures were prepared from raw data kindly provided by Tilman Lamparter and Katsuhiko Inomata (Inomata et al, 2005). assembled with phycoerythrobilin, a bilin that is missing the C15,16 double bond, are intensely fluorescent, nonphotoconvertible biliproteins (Li et al, 1995;Murphy and Lagarias, 1997). In the DrBphP structure, the BV D-ring is twisted out of plane relative to the A-, B-, and C-rings.…”
Section: Light Sensing and Signal Transduction: New Insightsmentioning
confidence: 99%
“…The wild-type BV adduct is shown in the Pr state (solid) and as a calculated pure Pfr spectrum (dashed line). Figures were prepared from raw data kindly provided by Tilman Lamparter and Katsuhiko Inomata (Inomata et al, 2005). assembled with phycoerythrobilin, a bilin that is missing the C15,16 double bond, are intensely fluorescent, nonphotoconvertible biliproteins (Li et al, 1995;Murphy and Lagarias, 1997). In the DrBphP structure, the BV D-ring is twisted out of plane relative to the A-, B-, and C-rings.…”
Section: Light Sensing and Signal Transduction: New Insightsmentioning
confidence: 99%
“…17 This 15Ea chromophore was also attached to the Agp1 apoprotein, and the adduct was found to be the P fr form of Agp1. 16 From these results, sterically locked chromophores will open new avenues of investigation concerning the stereochemistry and function of phytochrome chromophores both in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, size exclusion chromatograph of Agp1-M15 (the N-terminal 504 amino acids of Agp1) apoprotein adduct with compound 2a and the autophosphorylation of the Agp1 adduct with compound 2a showed that the stereochemistry of CD-ring moiety of P r form of natural Agp1 is 15Za. 16 Recently, we also prepared another derivative of the chromophore in which the stereochemistry of the CD-ring moiety is fixed to 15Ea. 17 This 15Ea chromophore was also attached to the Agp1 apoprotein, and the adduct was found to be the P fr form of Agp1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations